Optimizing fenugreek (Trigonella foenum-graecum L.) oil yield and compositions in intercropping through growth-promoting bacteria and mycorrhiza - Amiriyan Chelan, Zahra; Amini, Rouhollah; Dabbagh Mohammadi Nasab, Adel (Frontiers in Agronomy, 2024)
IntroductionBiofertilizers and intercropping are two main components in sustainable production systems.Materials and methodsA two-year (2020–2021) study was conducted in East Azarbaijan, Iran, to evaluate the effects of arbuscular mycorrhizal fungi (AMF), growth-promoting bacteria (GPB) and chemical fertilizer (CF) on fenugreek (Trigonella foenum-graecum L.) (F) oil yield and compositions in intercropping with Moldavian balm (Dracocephalam mobdavica L.) (MB). The cropping patterns included MB sole cropping, fenugreek sole cropping (F) and replacement intercropping ratios consisted of Moldavian balm : fenugreek (MB:F (1:1)), MB:F (2:2) and MB:F (4:2) and additive intercropping of MB:F (100:50).ResultsFor both years, among the intercropping patters, the highest seed and oil yields were obtained in MB:F (100:50) intercropping pattern treated with CF and AMF+GPB. In all cropping patterns except MB:F (4:2), the highest anthocyanin, total flavonoid, and mucilage contents were observed in plants received AMF+GPB. At all treatments, the linoleic, oleic, and linolenic acid were the main components of fenugreek oil. In MB:F (1:1), (2:2), (4:2), and (100:50) intercropping patterns, the linoleic acid content in AMF+GPB treatment, increased by 9.45%, 6.63%, 15.20%, and 7.82%, respectively, compared with sole fenugreek. The highest total land equivalent ratio (LERT) values were obtained in 2021 and MB:F (100:50) intercropping pattern treated with CF (1.70) and AMF+GPB (1.63).ConclusionsIn general, it could be concluded that MB:F (100:50) intercropping pattern treated with AMF+GPB improved the oil yield and unsaturated fatty acid contents of fenugreek compared with sole cropping and could be recommended in sustainable production systems.